DESCRIPTION OF MOTHER KNOWLEDGE AND ATTITUDE TO BASIC NEED OF NIFAS MOTHER IN BPM HERMIN EKOWATI REGENCY OF BOYOLALI - Atik Wahyu Listarini; Putri Kusumawati Priyono; Deliana Megawati (STIKES DUTAGAMA KLATEN, 2018)
Background: Mother Mortality Rate (MMR) in Indonesia in 2015 is still quite high as many as 6400 people. In 2015 one of MMR the cause is infection and breast inflammation, the prevention is deepening the knowledge and change the negative attitude into a positive attitude about the basic needs of postpartum. The results of preliminary study in December 2016 from interviews 4 postpartum got 3 respondents (75%) have good knowledge level, and 1 respondent (25%) have less knowledge level. Objectives: To determine the level of knowledge and postpartum attitude about the basic needs of postpartum mothers Research method: This research uses quantitative descriptive method, with cross sectional research design. This research was conducted at BPMHermin Ekowati Tawangsari Hamlet, Ngenden Village, Ampel District, Boyolali District in May-June 2017. The population is a sample with the technique of purposive sampling. The research instrument used questionnaire on the variables of knowledge and attitude variable. Analysis of univariate analysis. Research Result: Knowledge of postpartum mother in BPM Hermin Ekowati Tawangsari Hamlet, Ngenden Village, Ampel District, Boyolali District have sufficient level of knowledge about basic need of postpartum mother as many as 19 people (54.3%) and attitude about basic need of postpartum majority have positive attitude 27 persons (77.1%). Conclusion:The most of knowledge level postpartum mother is knowledgeable enough and the attitudes toward the basic needs of postpartum mother has a positive attitude.